2017
DOI: 10.1093/mnras/stx532
|View full text |Cite
|
Sign up to set email alerts
|

A Kennicutt–Schmidt relation at molecular cloud scales and beyond

Abstract: Using N -body/gasdynamic simulations of a Milky Way-like galaxy we analyse a Kennicutt-Schmidt relation, Σ SFR ∝ Σ gas N , at different spatial scales. We simulate synthetic observations in CO lines and UV band. We adopt the star formation rate (SFR) defined in two ways: based on free fall collapse of a molecular cloud -Σ SFR, cl , and calculated by using a UV flux calibration -Σ SFR, UV . We study a KS relation for spatially smoothed maps with effective spatial resolution from molecular cloud scales to severa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Onodera et al (2010) found that the scatter of the KS relation increases on smaller scales until it breaks completely on the scale of molecular clouds (80 pc scales). The breakdown of the KS relation on small scales has also been demonstrated in dwarf galaxies (Krumholz 2013), in spiral galaxies (Khoperskov & Vasiliev 2017), and recently in some observational studies (Salim et al 2020;Kumari, Irwin & James 2020). Additionally an increasing number of studies suggest that this relation varies between different galaxies, and even within different regions of the same galaxy (Roman-Duval et al 2016;Morokuma-Matsui & Muraoka 2017).…”
mentioning
confidence: 73%
“…Onodera et al (2010) found that the scatter of the KS relation increases on smaller scales until it breaks completely on the scale of molecular clouds (80 pc scales). The breakdown of the KS relation on small scales has also been demonstrated in dwarf galaxies (Krumholz 2013), in spiral galaxies (Khoperskov & Vasiliev 2017), and recently in some observational studies (Salim et al 2020;Kumari, Irwin & James 2020). Additionally an increasing number of studies suggest that this relation varies between different galaxies, and even within different regions of the same galaxy (Roman-Duval et al 2016;Morokuma-Matsui & Muraoka 2017).…”
mentioning
confidence: 73%
“…These scales are at the limit of the assumption on which the balance between star formation laws and energy output still holds (e.g. Kravtsov 2003;Khoperskov & Vasiliev 2017;Schruba et al 2010). In Sec.…”
Section: Spatially Resolved Sed Fittingmentioning
confidence: 99%
“…The star formation law (Σ SFR ∝ Σ N gas ) has received considerable attention (Schmidt 1959;Kennicutt 1998a;Kravtsov 2003;Schaye & Dalla Vecchia 2008). However, only recently has it become possible to study scales down to 30 pc and address on what physical scales the star formation law holds and possibly even breaks down (Kravtsov 2003;Onodera et al 2010;Schruba et al 2010;Kruijssen & Longmore 2014;Khoperskov & Vasiliev 2017).…”
Section: Spatial Resolution Of the Sfmsmentioning
confidence: 99%